2018
DOI: 10.1038/s41598-018-24339-6
|View full text |Cite
|
Sign up to set email alerts
|

In vitro Cortical Network Firing is Homeostatically Regulated: A Model for Sleep Regulation

Abstract: Prolonged wakefulness leads to a homeostatic response manifested in increased amplitude and number of electroencephalogram (EEG) slow waves during recovery sleep. Cortical networks show a slow oscillation when the excitatory inputs are reduced (during slow wave sleep, anesthesia), or absent (in vitro preparations). It was recently shown that a homeostatic response to electrical stimulation can be induced in cortical cultures. Here we used cortical cultures grown on microelectrode arrays and stimulated them wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 60 publications
2
32
0
Order By: Relevance
“…The synchronous slow oscillation appears to be the inherent property of cortical neuron assemblies because the oscillation can be found in ex vivo cortical slabs/slices ( Sanchez-Vives and McCormick, 2000 ; Timofeev et al, 2000 ). It was even shown that the cultured neurons exhibit a synchronous firing pattern similar to that of slow oscillation, and the synchronous firing pattern can be converted to asynchronous one by applying chemical(s) including excitatory neurotransmitters ( Hinard et al, 2012 ; Kaufman et al, 2014 ; Saberi-Moghadam et al, 2018 ). Overall, the synchronous slow oscillation of cortical neurons can be modulated through multiple layers of neurotransmitters, brain circuits, and neuronal networks.…”
Section: Hierarchical Organization Of Circadian Clocks and Sleep Homementioning
confidence: 99%
See 1 more Smart Citation
“…The synchronous slow oscillation appears to be the inherent property of cortical neuron assemblies because the oscillation can be found in ex vivo cortical slabs/slices ( Sanchez-Vives and McCormick, 2000 ; Timofeev et al, 2000 ). It was even shown that the cultured neurons exhibit a synchronous firing pattern similar to that of slow oscillation, and the synchronous firing pattern can be converted to asynchronous one by applying chemical(s) including excitatory neurotransmitters ( Hinard et al, 2012 ; Kaufman et al, 2014 ; Saberi-Moghadam et al, 2018 ). Overall, the synchronous slow oscillation of cortical neurons can be modulated through multiple layers of neurotransmitters, brain circuits, and neuronal networks.…”
Section: Hierarchical Organization Of Circadian Clocks and Sleep Homementioning
confidence: 99%
“…The role of mammalian ERK as a sleep-promoting kinase may lie in the control of gene expression associated with sleep-wake cycle. This notion was demonstrated through unique studies using cultured cortical neurons, which show electrophysiological activity similar to slow oscillation, together with the homeostatic recovery response to the administration of chemical/electrical stimulation ( Hinard et al, 2012 ; Saberi-Moghadam et al, 2018 ). The cortical neurons also show altered gene expression by chemical stimulation mimicking the awake state.…”
Section: Phosphorylation-dependent Control Of the Sleep-wake Cyclementioning
confidence: 99%
“…Lower spike firing generally typical of sleep is thought to be due, at least in part, to regular periods of widespread synchronous network silence, termed off periods, intruding on ongoing activity ( Steriade et al, 1993b ; Steriade et al, 2001 ; Sanchez-Vives and Mattia, 2014 ). Importantly, off periods in neural populations are thought to underpin slow wave dynamics at the level of the field potential ( Steriade et al, 1993a ; Massimini et al, 2004 ; Buzsáki et al, 2012 ), and it was shown that their properties reflect homeostatic sleep need ( Vyazovskiy et al, 2009 ; McKillop et al, 2018 ; Saberi-Moghadam et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated that embryonic cortical neurons on MEA are able to recapitulate some essential features of sleep in a controllable way (I. Colombi et al, 2016; Hinard et al, 2012; Saberi-Moghadam, Simi, Setareh, Mikhail, & Tafti, 2018). Here, we treated cortical cultures with CCh to change the synchronized default sleep-like state, characterized by slow-wave oscillations typical of NREM sleep, into a theta-predominant state, which is typical of REM sleep.…”
Section: Discussionmentioning
confidence: 99%